2017
DOI: 10.1080/08037051.2017.1378069
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of carotid-femoral pulse wave velocity progression in hypertensive patients over a 3.7 years follow-up

Abstract: the accelerated arterial aging in treated hypertensive subjects is in large measure explained by age and BP values. PWV changes over time would probably give important information that need further future research studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…None of the participants had a diastolic blood pressure above 90 mmHg. Blood pressure is included in the examination of PWV and AIX, and is an important predictor of increasing PWV in follow-up studies [35]. Significant differences in some of the lipid biomarker concentrations were seen between males and females (CHOL and Apo B/Apo A-1 ratio).…”
Section: Resultsmentioning
confidence: 99%
“…None of the participants had a diastolic blood pressure above 90 mmHg. Blood pressure is included in the examination of PWV and AIX, and is an important predictor of increasing PWV in follow-up studies [35]. Significant differences in some of the lipid biomarker concentrations were seen between males and females (CHOL and Apo B/Apo A-1 ratio).…”
Section: Resultsmentioning
confidence: 99%
“…There are likely to be a number of factors contributing to age-related WMH progression. Meani et al (2018) observed the largest increase in pulse wave velocity (PWV), a measure of carotid stiffness, in the seventh decade [ 45 ]. PWV increased 1.8 m/s over an average of 3.7 years in individuals between 61 and 70.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence available to date would indicate that traditional risk factors, such as BMI, age, BP, homocysteine levels and serum lipids have strong associations with the progressions of PWV and IMT. For example, Meani et al [13] enrolled 333 hypertensive outpatients and followed 3.7 years, and showed that age, baseline BP were independent predictors of ΔPWV. Similarly, Huang et al [37] analyzed the data from 712 stroke-free and myocardial infarction-free Chinese participants at baseline and after an average interval of 4.3 years.…”
Section: Discussionmentioning
confidence: 99%